Zinc Fractions and Their Relationship with Soil Properties in Rice Growing Soils of South Kashmir - M.H. Chesti (Journal of the Indian Society of Soil Science, 2022)
A study was carried out during 2020-2021, to quantify different fractions of zinc (Zn) in rice growing soilsof Kashmir valley. The area delineated for study was Anantnag and Kulgam districts located in South ofKashmir valley, owing to the fact that rice is the staple food of the valley grown on a large scale in thisregion. Ninety surface soil samples (0-25 cm), forty five from each district were collected and analyzed forvarious Zn fractions and soil properties. The sequential extraction scheme was used to fractionate Zn intowater soluble-Zn, exchangeable-Zn, organically complexed-Zn, amorphous sesquioxide bound-Zn,crystalline sesquioxide bound-Zn and residual-Zn. The total-Zn was calculated as the sum of all the fractionswhich varied from 58.9 to 65.6 and 56.4 to 58.2 mg kg-1, respectively for the districts Anantnag andKulgam. The labile fractions such as water soluble (1%) and exchangeable Zn (2-3%) contributed verylittle to total-Zn, whereas residual-Zn was the most dominant fraction, accounting for 69 to 72% of total-Zn. Among the physicochemical properties, soil pH and organic carbon were the key factors that governedthe distribution of Zn in different chemical pools in both the districts.